Implementation of peer recovery coach services for opioid overdose patients in emergency departments in Indiana: findings from an informal learning collaborative of stakeholders - Staton, Monte D (Transl Behav Med, 2021)
The Recovery Coach and Peer Support Initiative (RCPSI) in Indiana focused on implementing peer recovery coaches (PRCs) to engage opioid overdose patients in emergency department (ED) settings and promote entry into recovery services. State workers and researchers organized an informal learning collaborative primarily through teleconference meetings with representatives of 11 health service vendors to support implementation. This study presents qualitative analysis of the teleconference meeting discussions that guided RCPSI implementation to display how the informal learning collaborative functioned to support implementation. This informal learning collaborative model can be applied in similar situations where there is limited guidance available for a practice being implemented by multidisciplinary teams. Authors conducted a thematic analysis of data from 32 stakeholder teleconference meetings held between February 2018 and April 2020. The analysis explored the function of these collaborative teleconferences for stakeholders. Major themes representing functions of the meetings for stakeholders include: social networking; executing the implementation plan; identifying and addressing barriers and facilitators; educating on peer recovery services and target population; and working through data collection. During the last 2 months of meetings, stakeholders discussed how the COVID-19 pandemic created multiple barriers but increased use of telehealth for recovery services. Teleconference meetings served as the main component of an informal learning collaborative for the RCPSI through which the vendor representatives could speak with each other and with organizers as they implemented the use of PRCs in EDs.